2021
DOI: 10.3389/fchem.2021.610738
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Formation Mechanism of Microdroplets on Pure Iron

Abstract: The electrochemical formation mechanism of microdroplets formed around a primary droplet of 3.5% NaCl solution on an iron-plated film was investigated by quartz crystal microbalance (QCM) and concentric three-electrode array (CTEA) measurements. During the initial stage, the microdroplets mainly originate from evaporation owing to cathodic polarization and electric current of the localized corrosion cell under the primary droplet. The maximal electrochemical potential difference between the anode and cathode w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Spreading occurred at the same high speed on both sides (about 4 mm/h) and then stopped after about 30 min, keeping a circular contact line. Another interesting feature is a thin superficial propagating front with the formation of peripheral micro-droplets, in agreement with the previous observations of Tsuru et al 21 , 25 . Tang et al .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Spreading occurred at the same high speed on both sides (about 4 mm/h) and then stopped after about 30 min, keeping a circular contact line. Another interesting feature is a thin superficial propagating front with the formation of peripheral micro-droplets, in agreement with the previous observations of Tsuru et al 21 , 25 . Tang et al .…”
Section: Resultssupporting
confidence: 91%
“…Tang et al . suggested that the initiation and propagation of these micro-droplets could influence the corrosion process in itself 25 . Side views allowed us to monitor the front position X front versus time on both sides of the droplet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies have revealed that cathodic polarization accelerates micro-droplet formation regardless of metal type, electrolyte species, composition of air, and environmental humidity. Additionally, Tang et al [35] developed a mechanical model for micro-droplet formation consisting of three steps: (i) horizontal movement from the primary droplet along the metal surface, (ii) evaporation from the primary droplet and recondensation on the metal surface, and (iii) condensation of moisture from the air. Bian et al [36], on the other hand, studied the change in the coverage range of micro-droplets on metal surfaces during early atmospheric corrosion through optical microscopy.…”
Section: Introductionmentioning
confidence: 99%